Head-to-head comparison of NT-proBNP and soluble ST2 for long-term prognosis of patients with hypertrophic cardiomyopathy. (14th October 2021) - Cediel Calderon, G; Resta, H; Codina, P; Santiago-Vacas, E; Domingo, M; Spitaleri, G; Lupon, J; Bayes-Genis, A
Abstract: Background: N-terminal pro-brain natriuretic peptide (NT-proBNP) predicts mortality and the development of heart failure (HF) in hypertrophic cardiomyopathy (HCM), however, evidence regarding soluble interleukin-1 receptor-like 1 (ST2) in this population is lacking. Purpose: To assess the ST2 and NT-proBNP significance for risk stratification of patients with HCM during long-term follow-up. Methods: We prospectively enrolled a cohort of consecutive patients with HCM admitted to an ambulatory HF Unit in a Tertiary University Hospital. All patients had clinical and echocardiographic evaluation and measurement of NT-proBNP and ST2 at inclusion. The primary endpoint was the composite of all-cause death or HF-related hospitalization. Results: 103 patients were enrolled, 68% (n=70) males with a median (IQR) age of 60 (50–71) years. The median (IQR) of ST2 was 31.5 (IQR: 24.5 – 40.7) pg/mL. During a median follow-up of 2.5 years, 17 patients had the primary endpoint. Both, NT-proBNP and ST2 (both log-transformed) were associated with the primary endpoint in the univariable analyses (p<0.01). However, after adjustment by age, sex, NYHA functional class and left ventricular ejection fraction (LVEF), this association remained statistically significant only for ST2 (HR: 4.62, 95% CI 1.80–11.87, p=0.001 vs HR: 1.57, 95% CI 0.97–2.54, p=0.068 for NT-proBNP). The addition of ST2 to a clinical model (age, sex, NYHA functional class and LVEF) increased the Harrel's C statistic from 0.70 to 0.76, while the addition of NT-proBNP increase this C-statistic only to 0.73. Conclusions: ST2 appears to be a valuable biomarker for the prediction of death and heart failure related hospitalization in patients with HCM, outperforming the prognostic value of NT-proBNP. Future research should delve into this association. Funding Acknowledgement: Type of funding sources: None.